A didactic system based on digital environmental sensors for decision-making training - Giacaglia, Giorgio Eugenio Oscare; Azzolino, José Luiz; Cruvinel, Paulo Estevão (Revista Ciências Exatas, 2008)
This paper presents a didactic system based on digital environmental sensors, which allow an educational platform for decision-making training on agricultural processes, with particular application in climatic risk analysis. It is organized with a module for data acquisition and signal processing for digital information and three additional modules dedicated respectively to wind speed [m/s], wind direction [], and pluviometric rate [mm] measurements. Besides, these modules having the sensors were assembled into a container made by transparent acrylic material, i.e., such arrangement allows not only the visualization of the transducers but also the electronic and mechanical hardware of the sensors during operation. Results are presented in terms of its practicality, reliability, and usefulness for training, as well as base for a complete method to formal education.